Invasive Argemone mexicana’s suppressive effects on germination and early growth of Triticum aestivum and Hordeum vulgare in South-western Saudi Arabia - Manal A. Alshaqhaa; Imen Souid; Manar D. Alshehri; Norah Alyahya; Kamel Msaada; Mounira Mkaddem Guedri (PLoS ONE, 2026)
The invasion of exotic plant species has emerged as a global problem that impacts the ecosystems, economy, and human health, and is the reason for biodiversity loss. Argemone mexicana L. is one of the plants that was recorded as an invasive plant species in south-western Saudi Arabia. Allelochemical properties have been stated but not empirically evaluated on economically important staple crops. In the present study, the phenotype of the A. mexicana L. plant was described using major and minor phenotypic morphology, and morphological seed. Additionally, laboratory experiments were conducted to evaluate the allelopathic effects of water extract of A. mexicana L. on radicle and plumule length of Triticum aestivum and Hordeum vulgare . Results showed that the allelopathic potential of leaf and seed extracts of A. mexicana decreased the seed germination (until 66.66%), plumule length (93.94%−94.94%), and radicle length (96.68%− 96.96%) respectively for T. aestivum and H. vulgare with a rise in extract concentration. Moreover, it was observed that the A. mexicana seed extract is more allelopathically effective than leaf extract. Hence, it could be concluded that the seed and leaf aqueous extracts contain water-soluble allelochemicals, which could inhibit seed germination of T. aestivum and H. vulgare .